Learning Model Islamic Education Environmentally-Based: Dukupuntang Junior High School Context - Akhmad Affandi; Mahbub Nuryadien (Ilmu Inovasi Nusantara, 2023)
Bobos Village, Dukupuntang District, and Cirebon Regency are some of the areas where there is a lot of environmental damage due to the exploitation of Mount Kuda, which is used as raw material for the housing industry. The resulting pollution causes pollution of the air, water, and soil. Junior High School (SMP) Negeri 1 Dukupuntang, Cirebon Regency, as one of the schools included in the Adiwiyata School, needs to develop environmental-based religious education for Islam. By using qualitative research methods whose data collection techniques use observation, in-depth interviews and documentation and analyzed using a qualitative data analysis interactively through the process of reduction, data display, and verification, it can be concluded that Environmental-based Islamic Education learning in the context of the 2013 Curriculum can be applied to schools with educational unit levels both Elementary School (SD), Junior High School (SMP), Senior High School (SMA) and Higher Education by referring to the objectives, materials, methods, media and eveluations both in the Learning Implementation Plan (RPP) or Semester Learning Plan (RPS) for Higher Education or in more importantly in the Implementation His (PP) learning